2009
DOI: 10.1016/j.bbr.2008.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Does 5-bromo-2′-deoxyuridine (BrdU) disrupt cell proliferation and neuronal maturation in the adult rat hippocampus in vivo?

Abstract: 5-Bromo-2′-deoxyuridine (BrdU) is frequently used as a mitotic marker in studies of cell proliferation. Recent studies have reported cytotoxic effects of BrdU on neural progenitor cells in embryonic and neonatal brains in vivo and in adult tissue studied in vitro. The present study was conducted to assess whether BrdU interferes with cell proliferation and neuronal maturation in the rat adult hippocampus in vivo. BrdU effects across a wide range of doses (40 – 480 mg/kg) on cell proliferation and the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
5
18
0
Order By: Relevance
“…The concentration of BrdU has an effect on cell proliferation across a wide range of doses depending on the way of application (40-480 mg/kg for i.p., and up to 2.5 g/kg for subcutaneous application) as reported in the literature [19,20]. Our study demonstrated that s.c. application of 200 mg of BrdU per animal is optimal for adequate labeling of proliferating cells in adult rats.…”
Section: Discussionsupporting
confidence: 86%
“…The concentration of BrdU has an effect on cell proliferation across a wide range of doses depending on the way of application (40-480 mg/kg for i.p., and up to 2.5 g/kg for subcutaneous application) as reported in the literature [19,20]. Our study demonstrated that s.c. application of 200 mg of BrdU per animal is optimal for adequate labeling of proliferating cells in adult rats.…”
Section: Discussionsupporting
confidence: 86%
“…Like fate mapping methods also BrdU-labeling has its limitations as long pulses with high doses of the thymidine analog could lead to an overdose and therefore to increased cell death. Despite the low dose of BrdU used in this study which is below doses previously described to have no toxic effects in the adult brain (Cameron and McKay, 2001;Hancock et al, 2009), we can not fully exclude minor effects on cell survival (not detected by Caspase-3 or DAPI stainings) for the long BrdU application.…”
Section: Progeny Of Ng21 Progenitorsmentioning
confidence: 61%
“…The highest tested dose (250mg/kg) marked a significantly higher density of cells than the lowest tested dose (50mg/kg). This finding supports previous studies of this relationship (Burns and Kuan, 2005;Cameron and Mckay, 2001;Hancock et al, 2009) and demonstrates that dose affects cell marking not only in mammalian species, but also in reptiles. In this experiment, the maximum BrdU dose was limited to 250mg/kg because BrdU precipitated from solutions containing more than 20mg/mL and injecting a large subcutaneous bolus (in excess of 21mL for a 1.2kg snake) is physically challenging, requiring multiple injection sites, which is potentially stressful to the animal.…”
Section: Dosage Of Brdusupporting
confidence: 92%
“…In accordance with previous studies (Cameron & McKay, 2001;Hancock et al, 2009), higher doses of BrdU should mark more newborn cells than lower doses. Based on previous studies of squamates, I expected higher cell proliferation and migration at the anterior olfactory bulb (AOB), medial cortex (MC), dorsoventricular ridge (DVR), and nucleus sphericus (NS) than in other regions (Font et al, 2001;Pérez-Cañellas and García-Verdugo, 1996).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation